Rolled-up magnetic microdrillers: towards remotely controlled minimally invasive surgery - Xi, Wang (2013)
Self-folded magnetic microtools with sharp ends are directed at enabling drilling and related incision operations of tissues, ex vivo, in a fluid with a viscosity similar to that of blood. These microtools change their rotation from a horizontal to a vertical one when they are immersed into a rotational magnetic field. Novel self-assembly paradigms with magnetic materials can enable the creation of remotely controlled and mass-produced tools for potential applications in minimally invasive surgery.